Edukasi Silvofishery Siput pada Kelompok Pengelola Mangrove di Desa Pangkalan Jambi, Bengkalis - Budijono, Budijono; Fauzi, Muhammad; Prianto, Eko; Putra, Ridwan Manda; Karnila, Rahman; Sumiarsih, Eni; Hendrizal, Andri; Efriyeldi, Efriyeldi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The snail silvofishery education in Pangkalan Jambi Village aims to equip mangrove management groups in combining mangrove conservation activities with the utilization of its economic value through the cultivation of Cerithidea obtusa snails, in order to create a balance of mangrove ecosystem services to improve the economy of coastal communities. The target group for this education is the “Harapan Bersama” Mangrove Management Group which is one of the fostered groups of PT. Kilang Pertamina Internasional (PT. KPI). The method used is lectures and tutorials as a result of discussions with the CSR team of PT. KPI. The implementation of education begins with the implementation of a pre-test, presentation of materials accompanied by interactive discussions and post-tests. At the end of the activity, a field review was carried out as a candidate for the silvofishery location. The result is that the implementation of this education is very interactive and gets a positive response from the target group who have long struggled to preserve and utilize the mangrove area through several activities, including planting mangrove seedlings and making abrasion prevention tools and producing mangrove products as well as a mangrove educational tourism village. However, this group does not yet know and understand this silvofishery as a form of environmentally friendly mangrove forest preservation and utilization. Post-activity evaluation has proven that this educational activity has increased the understanding of the target group to diversify their activities in the future. The implementation is to practice and assist the snail silvofishery activities in this group